2020
DOI: 10.1111/1346-8138.15317
|View full text |Cite
|
Sign up to set email alerts
|

Fatal neonatal nephrocutaneous syndrome in 18 Roma children with EGFR deficiency

Abstract: Epidermal growth factor receptor (EGFR) is a transmembrane glycoprotein with tyrosine-kinase signaling activity, involved in many cellular functions including cell growth and differentiation. Germ line loss-of-function mutations in EGFR lead to a severe neonatal skin disorder (Online Mendelian Inheritance in Man #131550). We report 18 premature Roma children from 16 families with birthweights ranging 440-1470 g and multisystem diseases due to the homozygous mutation c.1283G˃A (p.Gly428Asp) in EGFR. They presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 5 publications
0
16
0
Order By: Relevance
“…Exons of the SSBP1 gene (NM_001256510) were analysed by Sanger sequencing, exome sequencing proceeded as described previously [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…Exons of the SSBP1 gene (NM_001256510) were analysed by Sanger sequencing, exome sequencing proceeded as described previously [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…Dear Editor, We read with great interest the mutation report of fatal neonatal nephrocutaneous syndrome in 18 Roma children by Mazurova et al 1 Systemic inflammatory diseases caused by a germ line mutation in EGFR encoding epidermal growth factor receptor (EGFR) were first reported in 2014, as neonatal inflammatory skin and bowel disease (Online Mendelian Inheritance in Man #616069). 2 Later, Ganetzky et al 3 described a lethal syndrome of epithelial dysfunction with progeroid features caused by the identical EGFR mutation.…”
mentioning
confidence: 99%
“…2 Later, Ganetzky et al 3 described a lethal syndrome of epithelial dysfunction with progeroid features caused by the identical EGFR mutation. Mazurova et al 1 reported premature children with multisystem diseases, including one surviving 13-year-old boy with severe skin symptoms including ichthyosiform skin desquamation, as well as dentinogenesis imperfecta, Fanconi-like syndrome and secondary hyperaldosteronism. These findings extend the spectrum of EGFR mutations and provide further evidence for the genetic basis of disorders due to EGFR deficiency.…”
mentioning
confidence: 99%
See 2 more Smart Citations